1967
DOI: 10.1177/004051756703700305
|View full text |Cite
|
Sign up to set email alerts
|

Twist Flow in Ring Spinning

Abstract: A simple and easy method for measuring the twist density in the yarn between the roller-nip and thread-guide of a ring spinning frame has been compared with the high speed photography technique and has been shown to be reliable. Measurements using the method have brought out the influence of such factors as doff-stage, chase cycle, etc. on this twist density. It has been shown, for example, that there is, over the chase, a peri odic variation in the twist density—the maximum twist density is at the nose of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Our previous studies have provided the fundamentals of reducing yarn hairiness by adding just one static contact surface to hold fiber ends during the ring spun yarn formation process. 31 The single static contact surface may be not enough to hold the yarn hairs firmly during the re-wrapping onto the yarn surface; therefore, a self-adjustable disk surface is added to enhance the force of holding yarn surface hairs (Figure 1).
Figure 1.Diagram of the modified ring spinning system.
…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Our previous studies have provided the fundamentals of reducing yarn hairiness by adding just one static contact surface to hold fiber ends during the ring spun yarn formation process. 31 The single static contact surface may be not enough to hold the yarn hairs firmly during the re-wrapping onto the yarn surface; therefore, a self-adjustable disk surface is added to enhance the force of holding yarn surface hairs (Figure 1).
Figure 1.Diagram of the modified ring spinning system.
…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…The variation in twist density over a doff has been studied by Subramanian and others, 49 by taking a large number of readings from the start to the fi nish of the doff with the ring rail alternately at the nose and at the shoulder of the chase. The twist in the spinning zone is seen to be, on the whole, higher than the mechanical twist when the ring rail is at the nose of the chase, and always lower than the mechanical twist when the ring rail is at the shoulder of the chase.…”
Section: Variations In Twist Fl Ow Over a Doffmentioning
confidence: 99%
“…In order to clarify this point, Subramanian et al 49 measured twist density in the yarn in the spinning zone over a doff at four different chase positions. They observed that, over the chase, a periodic variation occurs in the twist density in the yarn in the spinning zone.…”
Section: Variations In Twist Fl Ow Within a Chasementioning
confidence: 99%
See 1 more Smart Citation
“…This study employs the short grooved surface-tocontact spinning strand within the conventional ring yarn formation zone (Figure 1(d)); according to a previous study, 17 the twist density of the spinning strand below the short grooved surface ( b ) increases, while twist density of the spinning strand contacting the short grooved surface ( c ) and the twist density of the spinning strand before entering the short grooved surface ( u ) decrease. The combination of the limited short grooved surface length (d) and the decreased c results in very limited rollings of spinning strands on the short grooved surface.…”
mentioning
confidence: 99%